Syntheses of Some Schiff Base Nematic Mesogens and the Study of Their Binary Phase Diagrams by Miscibility Experiments - Mohammed, Serwa A.; Yousif, Yousif Z. (Science Journal of University of Zakho, 2013)
The following four Schiff base compounds known to exhibit the nematic phase only have been prepared.(a)2-Hydroxy-4-Ethoxybenzylidene-4-Butylaniline(OH-EBBA).(b)4-Cyanobenzylidene-4-methoxyaniline (CNBMeOA). (c) 2-Hydroxy – 4 - Methoxybenzylidene-4-Butylaniline (OH-MBBA).(d) 4- Methylbenzylidene -4- cyanoaniline (MeBCNA). The compounds have been characterized by UV/VIS, IR, and Hʹ NMR spectra. Two binary systems were prepared. System 1, by mixing OH – EBBA and CNBMeOA; and system 2, by mixing OH –MBBA and MeBCNA. The liquid crystalline behavior of the prepared compounds and those of the mixtures of the two systems was studied by differential scanning calorimetry (DSC) and hot-stage polarized optical microscopy (POM). Comparative study on the binary phase diagrams of the two systems revealed that, the permanent dipole – induced dipole interactions responsible for the induced phases, semctic C (SmC) and smectic A (Sm A), over a long range of mole fractions, are much stronger in system 1 than in system 2 . An explanation for this behavior has been put forward.